2019
DOI: 10.1007/s10040-019-01962-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian evidential learning: validation à partir de tests expérimentaux d’injection-pompage

Abstract: Recent developments in uncertainty quantification show that a full inversion of model parameters is not always necessary to forecast the range of uncertainty of a specific prediction in Earth Sciences. Instead, Bayesian evidential learning (BEL) uses a set of prior models to derive a direct relationship between data and prediction. This recent technique has been mostly demonstrated for synthetic cases. This paper demonstrates the ability of BEL to predict the posterior distribution of temperature in an alluvia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…It is believed that the hydraulic conductivity of the aquifer and its variance are the most sensitive parameters of the model, as the sensitivity analysis results of a study undertaken in the same aquifer (but at another location) have shown. This study was carried out with similar parameters and boundary conditions, by performing and simulating a heat push-pull test [34]. Inverse modeling has been widely applied in previous research projects [31,73] and recent developments of Bayesian evidential learning techniques push forward the allowance for direct predictions to be performed based on prior models [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that the hydraulic conductivity of the aquifer and its variance are the most sensitive parameters of the model, as the sensitivity analysis results of a study undertaken in the same aquifer (but at another location) have shown. This study was carried out with similar parameters and boundary conditions, by performing and simulating a heat push-pull test [34]. Inverse modeling has been widely applied in previous research projects [31,73] and recent developments of Bayesian evidential learning techniques push forward the allowance for direct predictions to be performed based on prior models [34].…”
Section: Discussionmentioning
confidence: 99%
“…In Flanders, a decree on deep geothermal use was approved in 2016 and new regulations are expected to be implemented soon [27]. In Wallonia, efforts to develop ATES systems have been made [28,29], with several studies performed on shallow aquifer thermal injection and recovery highlighting some potential ATES target aquifers [30][31][32][33][34][35][36].Reproducing heat transport originating from ATES systems with numerical models has been successfully achieved by various authors [37]. By using the finite element FEFLOW modeling code [38,39], Bridger and Allen [40] simulated 3D seasonal ATES in a heterogeneous unconfined aquifer, highlighting thermal short-circuit issues, which were reported in several other studies [41,42].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Global sensitivity analysis is therefore applied to select a subset of the PCA orthogonalized m that is most informed by the data variables. The subset m may retain only a few principal components (PCs) (Hoffmann et al, 2019), depending on how informative the boreholes are. For unselected (non-sensitive) model variables, they remain random according to their prior empirical distribution.…”
Section: Reviewmentioning
confidence: 99%